Stock return determinants in Indonesia - Nurhayati, Enung; Hamzah, Amir; Nugraha, Helmi (Universitas Sam Ratulangi, 2021)
The purpose of this study is to provide empirical evidence regarding the effect of capital structure, company, size, earnings quality on stock returns with stock liquidity as an intervening variable. The method used in this study is descriptive and verification methods. This study uses 17 listed firms in Indonesia Stock Exchange as the sample specifically for the textile and garment industry over the period of 2014 to 2018 and analyzed by path analysis. The results show that capital structure, firm size, and earnings quality have significant and positive effects directly on stock returns and indirectly through stock liquidity. These findings imply that capital structure, firm size, earnings quality, and stock liquidity shall form positive information to investors under condition high trust of investors as the impact of decreasing asymmetric information. Consistent with signaling theory, this study proves that positive information on investors will be formed if there is an increase in investor confidence as a result of reduced information asymmetry.